What is the value of ab? (1) |a| + b = a (2) a + |b| = b

A. Statement (1) BY ITSELF is sufficient to answer the question, but statement (2) by itself is not. B. Statement (2) BY ITSELF is sufficient to answer the question, but statement (1) by itself is not. C. Statements (1) and (2) TAKEN TOGETHER are sufficient to answer the question, even though NEITHER statement BY ITSELF is sufficient. D. Either statement BY ITSELF is sufficient to answer the question. E. Statements (1) and (2) TAKEN TOGETHER are NOT sufficient to answer the question, meaning that further information would be needed to answer the question.

(C) Statement (1) is |a| + b = a. If 0 > a then |a| = -a. So the equation transforms into -a + b = a. This yields b = 2a. Therefore ab = 2a². But we do NOT know the value of a. So statement (1) by itself is NOT sufficient.

Statement (2) is a + |b| = b. Similarly to the previous reasoning, if 0 > b then |b| = -b. So the equation transforms into a – b = b. This yields a = 2b. Therefore ab = 2b². But we do NOT know the value of b. So statement (2) by itself is NOT sufficient. If we use the both statements together, we can add the equations. |a| + b + a + |b| = a + b |a| + |b| = 0 Any absolute value is non-negative. So the sum equals 0 if and only if each absolute value is 0. Therefore a = 0, b = 0 and ab = 0. Statements (1) and (2) taken together are sufficient to answer the question, even though neither statement by itself is sufficient. The correct answer is C. ---------- I did not understand the concept of |a| = -a.

This answer is really weird. In the question, it is not mentioned that "a" or "b" is a constant – which means " |a| + |b| = 0 " does not guarantee that a and b are "0". It could mean a = -b.

In the question, it is not mentioned that "a" or "b" is a constant …

a and b are variables.

Quote:

… " |a| + |b| = 0 " does not guarantee that a and b are "0" …

Any absolute value is non-negative. If a and b were not zeroes, then |a| would be positive and |b| would be positive. positive + positive > 0 That would contradict the equation. Even if only one variable was not zero, the left side would still be positive. So the both variables can possess only one value, 0.

Quote:

… It could mean a = -b.

If to plug in a = -b we will get |-b| + |b| as the left side of the equation. It is not necessarily 0. Plug any non-zero value for b, for example b = 2 yields |-2| + |2| = 2 + 2 = 4. So the conclusion "It could mean a = -b" is not correct.

If to solve the equation |-b| + |b| = 0: The absolute values |-b| and |b| are the same (equal), so the equation transforms into 2|b| = 0 b = 0

Statement (1) tells us that b is 0 and a must be positive, therefore ab = 0 (knowing b is 0 would be sufficient to answer the question and b has to equal 0 for the statement to be true).

Statement (2) tells us that a is 0 and b must be positive, therefore ab = 0. (knowing a is 0 would be sufficient to answer the question and a has to equal 0 for the statement to be true).

Users browsing this forum: No registered users and 5 guests

You cannot post new topics in this forum You cannot reply to topics in this forum You cannot edit your posts in this forum You cannot delete your posts in this forum You cannot post attachments in this forum

GMAT(TM) and GMAT CAT (TM) are registered trademarks of the Graduate Management Admission Council(TM). The Graduate Management Admission Council(TM) does not endorse, nor is affiliated in any way with the owner or any content of this site.